Co-Utilization of HIV, Substance Use, Mental Health Services Among Women With Current Substance Use: Opportunities for Integrated Care? - Ayako W. Fujita; Aditi Ramakrishnan; C. Christina Mehta; Oyindamola B. Yusuf; Azure B. Thompson; Steven Shoptaw; Adam W. Carrico; Adaora A. Adimora; Ellen Eaton; Mardge H. Cohen; Jennifer P. Jain; Adebola Adedimeji; et al. (SAGE Publishing, 2024)
Background: The syndemic of HIV, substance use (SU), and mental illness has serious implications for HIV disease progression among women. We described co-utilization of HIV care, SU treatment, and mental health treatment among women with or at risk for HIV. Methods: We included data from women with or at risk for HIV (n = 2559) enrolled in all 10 sites of the Women's Interagency HIV Study (WIHS) from 2013 to 2020. Current SU was defined as self-reported, non-medical use of drugs in the past year, excluding use of only marijuana. Tobacco and alcohol were assessed separately. We described co-utilization of SU treatment, tobacco and alcohol use treatment, HIV care, and mental health care in the past year among women who were eligible for each service. We compared service utilization by those who did/did not utilize SU treatment using Wald Chi-square tests. Results: Among women with current SU (n = 358), 42% reported utilizing SU treatment. Among those with current SU+HIV (n = 224), 84% saw their HIV provider, and 34% saw a mental health provider. Among women with current SU+heavy alcohol use (n = 95), 18% utilized alcohol use treatment; among current SU+tobacco use (n = 276), 8% utilized tobacco use treatment. Women who utilized SU treatment had higher utilization of alcohol use treatment (59% vs. 5%; P  < .001) and tobacco use treatment (12% vs. 5%; P  = .028). HIV care engagement was high regardless of SU treatment. Conclusions: We found high engagement in SU and HIV care, but low engagement in alcohol and tobacco use treatment. Integrated SU treatment services for women, including tobacco/alcohol treatment and harm reduction, are needed to optimize treatment engagement and HIV care continuum outcomes.